2017
DOI: 10.1007/s11262-017-1519-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and recombination analysis of porcine reproductive and respiratory syndrome virus emerged in southwestern China during 2012–2016

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is an important swine pathogen causing tremendous economic losses to the swine industry. To investigate the prevalence of PRRSV of genotype 2 (North American type, NA-type) in southwestern China, the Nsp2 hypervariable region (Nsp2 HV) and ORF5 of 61 PRRS viruses collected during 2012-2016 were sequenced and analyzed. All the virus detected clustered into the JXA1-like (52/61), VR-2332-like (7/61), and NADC30-like (2/61) sub-genotypes. Five deletions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…However, the complex recombination pattern among a NADC30-like, a JXA1-like, and the classical PRRSV-2-derived MLV vaccine strain (RespPRRS MLV) has never been described. In our previous investigation, we found that JXA1-like, NADC30-like, VR-2332-like, and QYYZ-like strains had coexisted in some pig herds in the Sichuan Province since 2016, and the following different recombination patterns were observed in this region: (i) NADC30-like + JXA1-like [ 23 ]; (ii)NADC30-like + JXA1-like + VR-2332-like [ 27 ]; and (iii) NADC30-like + JXA1-like + QYYZ-like [ 28 ]. This evidence thus further supported the possible recombination among the PRRSV strains, NADC30-like and JXA1-like, and the vaccine strain, RespPRRS MLV (VR-2332-like).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the complex recombination pattern among a NADC30-like, a JXA1-like, and the classical PRRSV-2-derived MLV vaccine strain (RespPRRS MLV) has never been described. In our previous investigation, we found that JXA1-like, NADC30-like, VR-2332-like, and QYYZ-like strains had coexisted in some pig herds in the Sichuan Province since 2016, and the following different recombination patterns were observed in this region: (i) NADC30-like + JXA1-like [ 23 ]; (ii)NADC30-like + JXA1-like + VR-2332-like [ 27 ]; and (iii) NADC30-like + JXA1-like + QYYZ-like [ 28 ]. This evidence thus further supported the possible recombination among the PRRSV strains, NADC30-like and JXA1-like, and the vaccine strain, RespPRRS MLV (VR-2332-like).…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR was used to confirm PRRSV positivity in suspensions of lung tissue homogenates, which were then inoculated into PAMs. The PAMs were maintained in RPMI-1640 medium (Transgene, Beijing, China) supplemented with 10% fetal bovine serum (HyClone, Logan, UT, USA) at 37 °C in a humidified 5% CO 2 atmosphere as described previously [ 23 ]. Indirect immunofluorescence assay (IFA) was performed to detect viral antigens in PAMs using GTX129270 (a monoclonal antibody against PRRSV N protein; GeneTex Inc., Irvine, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First-strand cDNA was synthesized using random hexamers (TaKaRa, Dalian, China) following the manufacturer’s instructions. The complete genomic sequences of SCcd17 were amplified with fourteen overlapping fragments by reverse transcription-PCR (RT-PCR) as described previously [ 32 ]. The PCR products were purified and cloned into pMD19-T vector (TaKaRa, Dalian, China) following the manufacturer’s instructions, and then sequenced at least three times by the commercial service (Sangon, Shanghai, China) using Sanger sequencing approach.…”
Section: Methodsmentioning
confidence: 99%